Equality and Diversity Value Incommensurability and the Politics of Recognition - Smith, Steven (Policy Press, 2011)
This important book explores the values of equality and diversity as promoted across liberal societies, drawing on various traditions of political and social philosophy, and applying them to policy and practice debates.